Assessment of online education problems during the COVID-19 pandemic in Russia - Ilshat Garafiev; Gulshat Garafieva; Angelika Idiatullina; Elena Spirchagova (Institute of Advanced Engineering and Science, 2021)
The work studied the assessment of online education problems during the COVID-19 pandemic by the first year master’s students. It was hypothesized that there are two types of problems. The first type is the problems associated with the difficulties of online communication between the participants of the educational process. The second type is the problems associated with the technical difficulties of participating in online education. The results of factor analysis show that masters clearly distinguish between the content-related (online communication) and formal (technical problems) sides of the organization of online education. It was found that those masters’ students who do not work now or do not have work experience in the specialty for which they are studying generally perceive the presence of technical problems and Internet disruptions as difficulties in implementing online education more significantly.